Răspuns :
Răspuns:
Explicație pas cu pas:
0,(6) = 6/9
54*6/9 = 36
√36 = 6
________
0,0(6) = 6/90
540*6/90 = 36
√36 = 6
________
0,00(6) = 6/900
5400*6/900 = 36
√36 = 6
________________
n = 6 + 6 + 6 = 18
[tex]\displaystyle\bf\\n=\sqrt{54\cdot0,(6)}+\sqrt{540\cdot0,0(6)}+\sqrt{5400\cdot0,00(6)}\\\\\\n=\sqrt{54\cdot\frac{6}{9}}+\sqrt{540\cdot\frac{6}{90}}+\sqrt{5400\cdot\frac{6}{900}}\\\\\\n=\sqrt{54\cdot\frac{6}{9}}+\sqrt{540\cdot\frac{6}{90}}+\sqrt{5400\cdot\frac{6}{900}}\\\\\\n=\sqrt{\frac{54\cdot6}{9}}+\sqrt{\frac{540\cdot6}{90}}+\sqrt{\frac{5400\cdot6}{900}}\\\\\\n=\sqrt{\frac{54\cdot6}{9}}+\sqrt{\frac{54\cdot6}{9}}+\sqrt{\frac{54\cdot6}{9}}[/tex]
.
[tex]\displaystyle\bf\\n=\sqrt{\frac{6\cdot9\cdot6}{9}}+\sqrt{\frac{6\cdot9\cdot6}{9}}+\sqrt{\frac{6\cdot9\cdot6}{9}}\\\\\\n=\sqrt{\frac{6\cdot9\cdot6}{9}}+\sqrt{\frac{6\cdot9\cdot6}{9}}+\sqrt{\frac{6\cdot9\cdot6}{9}}\\\\\\n=\sqrt{6\cdot6}+\sqrt{6\cdot6}+\sqrt{6\cdot6}\\\\\\n=\sqrt{36}+\sqrt{36}+\sqrt{36}\\\\\\n=6+6+6\\\\\\\boxed{\bf n=18}\\\\Raspuns~corect\!:~~C)~18[/tex]